Time course for the recovery of physical performance, blood hemoglobin, and ferritin content after blood donation. Issue 4 (16th December 2014) - Ziegler, Andreas K.; Grand, Johannes; Stangerup, Ida; Nielsen, Hans J.; Dela, Flemming; Magnussen, Karin; Helge, Jørn W.
<x xml:space="preserve">Abstract</x> Background It is widely accepted that blood donation negatively affects endurance performance, but data on physical recovery after a standard blood donation are scarce. This study aimed to elucidate the temporary impact of blood donation on endurance performance, measured as peak oxygen uptake (VO2peak) and time trial (TT) performance. Study Design and Methods VO2peak, TT performance, blood, iron, and anthropometric variables were determined before (baseline) and 3, 7, 14, and 28 days after blood donation in 19 healthy men. Results VO2peak was reduced by 6.5% from 49.7 ± 2 mL/kg/min at baseline to 46.3 ± 2 mL/kg/min on Day 3 (p < 0.001), and TT performance was reduced by 5.2% from 13:31 ± 00:42 to 14:13 ± 00:50 min:sec (p < 0.001). Both VO2peak and TT performance were back to baseline 14 days after blood donation. Blood hemoglobin (Hb) concentration declined 7.9% from 9.3 ± 0.11 mmol/L at baseline to 8.6 ± 0.1 mmol/L on Day 3 (p < 0.001) and was not different from baseline 28 days after blood donation. The hematocrit (Hct) was reduced from 43.8 ± 0.5% at baseline to 40.6 ± 0.6% on Day 3 (p < 0.001). On Day 28 Hct was 42.8 ± 0.5% and still reduced below baseline (p = 0.028). Ferritin concentration was reduced 46% from 113 ± 23 μg/L at baseline to a minimum of 61 ± 14 μg/L on Day 14 (p = 0.008). Conclusion The individual recovery was variable, but physical performance was recovered 14 days after a standard blood donation, despite blood Hb concentration remaining lower than at baseline.